Difference in drug cost between private and public drug plans in Quebec, Canada - Chamoun M.; Forget A.; Chabot I.; Schnitzer M.; Blais L. (BMC, 2022)
Abstract Background We expect a difference in drug cost between private drug plans and the Public Drug Plan (PDP) because the dispensing fee is fixed and regulated by the PDP for publicly insured patients, whereas it is determined freely by the pharmacy owner for privately insured patients. This study compared the drug cost of Quebec residents covered by private drug plans with those covered by PDP. Methods We used a sample of prescriptions filled between 1 January 2015 and 23 May 2019 selected from reMed, a database of Quebecers' drug claims. We created strata of prescriptions filled by privately insured patients and matched them with strata of prescriptions filled by publicly insured patients based on the Drug Identification Number, quantity dispensed, number of days of supply, pharmacy identifier, and a date corresponding to the publication of List of Medications of Régie de l'Assurance Maladie du Québec. The differences in drug cost between private plans and the PDP were analyzed with linear regression models using prescription strata as the unit of analysis. Results Based on 38 896 prescription strata, we observed that privately insured patients payed $9·35 (95% confidence interval [CI]: 5·58; 13·01) more on average per drug prescription than publicly insured patients, representing a difference of 17·6%. Conclusions This study showed that, on average, drug cost is substantially higher for privately insured Quebecers. Knowing that adherence to treatment is affected by drug cost, these results will help public health authorities to make informed decisions about drug policies.